What we know and what we need to know about graduate skills - James, S; Warhurst, C; Tholen, G; Commander, J (2013)
The expansion of higher education has led to more graduates in the UK labour market. Despite government expectations, this expansion has not boosted national economic competitiveness. This article argues that current understanding of the impact of graduates' skills is limited by methodological and conceptual narrowness in current research and that a broader research agenda is required. This agenda needs to cover not just the supply but also the demand, development and deployment of graduates' skills and, as a consequence, distinguish between 'graduate skills' acquired in higher education and the 'skills of graduates' formed prior to, in and parallel to higher education. © The Author(s) 2013.